Factors influencing the intention to invest in Malaysia environmental, social, and governance (ESG) mutual funds - Chai, Pei Lin; Khong, Jing Yuan; Priyanka, Manimaran (2025)
Environmental, Social and Governance (ESG) investing is gaining global prominence as investors seek sustainable options that align with their values while generating returns, yet Malaysian investors remain hesitant toward ESG mutual funds despite growing environmental and governance concerns. This study examines factors influencing Malaysian investors' intention to invest in ESG mutual funds using the Theory of Planned Behaviour (TPB), collecting data from 407 Malaysian adults aged 18 and above through questionnaires. The study examined relationships between environmental and societal awareness, expected returns, social influence, personal values, investment experience, fund management reputation, and financial risk level with ESG investment intention. Results indicate that fund management reputation and financial risk level significantly and positively influence ESG investment intention, while environmental and societal awareness, expected returns, social influence, personal values, and investment experience showed no significant influence. The findings suggest that fund managers, financial institutions, and policymakers should focus on management reputation and risk communication when promoting ESG mutual fund adoption among Malaysian investors.